Laparoscopic hernioplasty of large ventral hernia with transfascial sutures: short term utility and outcome - A Kumar (Society of Surgeons of Nepal, 2016)
Introduction: The laparoscopic approach to repairing ventral and incisional hernias has gained increasing popularity worldwide. The approximation of the hernia defect during laparoscopic ventral hernia repair, prior to mesh fixation, provides a more physiologic and anatomic repair. Defect closure also provides more defect overlap with mesh placement and, possibly decreases recurrence rates. We reviewed the experience of laparoscopic repair of large ventral hernia (diameter ≥5cm) at a university hospital in the Nepal with particular reference to patients with massive defects (diameter ≥15cm) and transfascial closure.